Roofman [videorecording (DVD)] - Cianfrance, Derek; Gunn, Kirt; Tatum, Channing; Dunst, Kirsten, 1982-; Mendelsohn, Ben; Stanfield, LaKeith, 1991-; Temple, Juno, 1989-; Diaz, Melonie; Aduba, Uzo; Collias, Lily; Yang, Jimmy O.; Dinklage, Peter (Paramount, 2026)
Based on an unbelievable true story, Roofman follows Jeffrey Manchester, an Army veteran and struggling father who turns to robbing McDonald's restaurants by cutting holes in their roofs, earning him the nickname: Roofman. After escaping prison, he secretly lives inside a Toys "R" Us for six months, surviving undetected while planning his next move. But when he falls for Leigh, a divorced mom drawn to his undeniable charm, his double life begins to unravel, setting off a compelling and suspenseful game of cat and mouse as his past closes in.